Comparative study of the characteristics of the energy flow and food web structure in the Laizhou Bay ecosystem based on the Ecopath and LIM-MCMC models - Wenhui, Cui; Bingqing, Xu; Xiuqiang, Dong; Jisong, Yang; Min, Li; Depu, Zhang; Shengfu, Li; Zhenbo, Lv; Fan, Li; Zhonghua, Ren (Frontiers in Marine Science, 2025)
This study compared the characteristics of energy flow and food web structure in the Laizhou Bay ecosystem using the Ecopath model and linear inverse models enhanced by Monte Carlo methods coupled with a Markov Chain (LIM-MCMC), respectively, based on survey data collected in May, August, and November 2022. The ecosystem was divided into 22 functional groups with trophic levels ranging from 1.00 to 3.48 and a large proportion of predator groups. The Ecopath model estimated an overall energy transfer efficiency of 5.34%, with the detrital food chain exhibiting significantly higher energy transfer efficiency (6.73%) than the grazing food chain (5.31%). Energy flow paths in the LIM-MCMC model were classified into four primary routes, predominantly driven by respiration and the inflow of detritus at lower trophic levels, which accounted for 79.9% of the total energy flow in group a. The Ecopath model provided a connectance index of 0.30, a system omnivory index of 0.33, Finn’s mean path length of 2.46, and Finn’s cycle index of 8.18%, whereas the LIM-MCMC model produced an average path length of 2.78. Both models indicated a shorter food chain and low complexity of the food web. Total system throughput (TST) was estimated at 10,086.1 (Ecopath) and 10,968.0 t·km-2a-1(LIM-MCMC), with total respiration and total flows into detritus accounting for 41.2% and 51.1% of TST, respectively. The total primary production to total respiration ratios were 1.40 (Ecopath) and 0.86 (LIM-MCMC). Despite consistent ecosystem parameters across both models—total consumption (4,407.7 t·km-2a-1), total primary production (3,606.4 t·km-2a-1), and total biomas (151.0 t·km-2a-1)—the Ecopath model suggested a relatively mature ecosystem, whereas the LIM-MCMC model indicated that this ecosystem was in an unstable developmental stage with low energy utilisation efficiency of primary productivity